SIMULASI GELOMBANG BERJALAN DENGAN MENGGUNAKAN SOFTWARE MATLAB VERSI 7.14 - Faruq, Fauzi al; Lanto, Muhammad Said; Hernawati, Hernawati (JFT: Jurnal Fisika dan Terapannya, 2014)
Walking With Wave Simulation Using MATLAB Software Version 7:14. The purpose of this study wasto visualize the simulation program in the two-dimensional wave propagation, waveforms are in phase and phase difference and interference of waves in the wave superposition and wave visualization using MATLAB. This study uses a hardware specification that is a notebook with an Intel ® Core TM i3-380M, 2 GB DDR3 Memory, 320 GB HDD, Windows 7 Professional 32-bit system and the software Matlab & Simulink Release 2012a version 7.14. Making simulation starts from collecting multiple variables from multiple reference wave. The study was conducted by making the program compilers and program display the caller in the script M-file in the software matlab. Then execute all forms of variable wave existing programs in M-files in Matlab and explains all the waveforms are executed.